Adhesion of Polymorphonuclear Leukocytes to Protein-Coated and Platelet Adherent Surfaces - Morley, D J; Feuerstein, I A (Thrombosis and Haemostasis, 1989)
Since protein adsorption and platelet adhesion are likely to precede significant contact of leukocytes with the surfaces of artificial organs, we have chosen to study polymorphonuclear leukocyte (PMN) adhesion in a sequential manner. The work presented here deals with the effects of flow and surface type on PMN adhesion to fibrinogen- and albumin-coated glass. We compared direct adhesion to adsorbed protein with adhesion to adsorbed protein having adherent platelets. These experiments were designed to see if PMN's might preferentially adhere to albumin or fibrinogen and whether a particular morphological form of adherent platelet could promote PMN adhesion. The adhesion of PMN's to spread platelets on albumin or fibrinogen occurs to a greater extent than in the absence of platelets. Adhesion of PMN's to spread platelets may be an important mechanism for their depletion from the circulation during artificial organ use. .
Keywords: Albumin; Fibrinogen; Platelet adhesion; Polymorphonuclear leukocyte adhesion